Kompetensi Aparatur Dalam Pelaksanaan Desentralisasi Dan Otonomi Daerah - Deddy Supriady Bratakusumah (Centre for Public Policy and Management Studies, 2002)
Historically, there are rules that followed pasal 18 UUD 1945. the arise of rules No 22 and 25 /1999 based on TAP MPR No XV/MPR/1998, it is occurred because there are many constraints that are facing by the rules No 5/1974 and then opportunities that are realized by the government and the representative of the people to exercise decentralization and autonomy. The opportunities are realized by them, such as the effort of reformation, the strong need of democratization and decentralization, free trade, globalization etc.Rule No 22/1999 explicitely separate the autonomy between the central government and the local govemment. it is also declare the autonomy of the local government is to manage it's own region in order to the public service in it's own region.The rule No 25/1999 is made to complete the rule No 22/1999. Local government should realized that autonomy which is given to the local government costly. Local government should reanalyze and reidentify the source of the local income to increase local income and in order to exercise decentralization.The exercise of decentralization needed financial decentralization, it means that government need human resources that are competent and professional to increase the source of the local income and how to used it in local region. Education and trainings is a tool that can be used to increase the capabilities of the apparatus. Should be note, that the education and the training that are exercised before is not a good tool because it can fullfilled the need of their task. So education and training that will be used should be analyzed it's own goals, such as what is the standard to become a good civil servant. The civil servant that are competent and professional is one of the basic tools that can help local government to increase public service and public welfare.